Synthesis of a Potent Pan-Serotype Dengue Virus Inhibitor Having a Tetrahydrothienopyridine Core - Hung, Kevin; Liu, Yugang; Simon, Oliver; Zhang, Lei; Lu, Peichao; Yeung, Bryan K. S.; Sarko, Christopher; Yokokawa, Fumiaki (Synlett, 2020)
A synthesis of the first-in-class pan-serotype dengue virus inhibitor NITD-688 is presented. The Gewald reaction of N-(tert-butoxycarbonyl)-6,6-dimethylpiperidin-3-one with malononitrile and sulfur in the presence of l-proline as a catalyst gave tert-butyl 2-amino-3-cyano-6,6-dimethyl-6,7-dihydrothieno[3,2-c]pyridine-5(4H)-carboxylate. This was coupled with [4-(aminosulfonyl)phenyl]acetic acid by using propanephosphonic acid anhydride. A subsequent reductive alkylation with cyclohexanecarboxaldehyde gave NITD-688. Preliminary results of our attempts to control the regioselectivity of the Gewald synthesis of the 2-amino-3-cyanothiophene core are also presented.
Keywords: medicinal chemistry; Gewald reaction; tetrahydrothienopyridines; regioselectivity; dengue virus inhibitors